Modified von Kármán equations for elastic nanoplates with surface tension and surface elasticity. (January 2017) - Yue, Y.M.; Ru, C.Q.; Xu, K.Y.
Abstract: In this paper, modified von Kármán equations are derived for Kirchhoff nanoplates with surface tension and surface tension-induced residual stresses. The simplified Gurtin-Murdoch model which does not contain non-strain displacement gradients in surface stress-strain relations is adopted, so that the von Kármán strain-compatibility equation can be expressed in terms of the stress function and deflection. The modified von Kármán equations derived here are different than the existing related models especially for elastic plates with in-plane movable edges. Unlike the existing models which predict a surface tension-induced tensile pre-stress for an elastic plate with in-plane movable edges, the present model predicts that this tensile pre-stress is actually cancelled by the surface tension-induced residual compressive stress. Our this result is consistent with recent clarification on similar issue for cantilever beams with surface tension, which implies that the existing models have incorrectly predicted an invalid tensile pre-stress for an elastic plate with in-plane movable edges which leads to significant overestimation of postbuckling load and free vibration frequencies. In addition, our numerical examples indicated that surface stresses can moderately increase or decrease postbuckling load and free vibration frequency of Kirchhoff nanoplate with all in-plane movable edges, depending on the surface elasticity parameters and the geometrical dimensions of nanoplates. Highlights: The surface model contains surface elasticity, surface tension and surface tension-induced residual stresses. Modified von Kármán equations are derived for Kirchhoff nanoplates with surface effects. Distributions of surface tension-induced residual stresses in the plates depend on the boundary conditions. Neglecting surface tension-induced residual stresses may lead to overestimate the surface effect.